Factors associated with postpartum psychiatric admission in a population‐based cohort of women with schizophrenia. (20th July 2016) - Vigod, S. N.; Rochon‐Terry, G.; Fung, K.; Gruneir, A.; Dennis, C.‐L.; Grigoriadis, S.; Kurdyak, P. A.; Ray, J. G.; Rochon, P.; Seeman, M. V.
Abstract : Objective: We aimed to identify factors associated with postpartum psychiatric admission in schizophrenia. Method: In a population‐based cohort study of 1433 mothers with schizophrenia in Ontario, Canada (2003–2011), we compared women with and without psychiatric admission in the 1st year postpartum on demographic, maternal medical/obstetrical, infant and psychiatric factors and identified factors independently associated with admission. Results: Admitted women ( n = 275, 19%) were less likely to be adolescents, more likely to be low income and less likely to have received prenatal ultrasound before 20 weeks gestation compared to non‐admitted women. They also had higher rates of predelivery psychiatric comorbidity and mental health service use. Factors independently associated with postpartum admission were age (<20 vs. ≥35 years: adjusted risk ratio, aRR, 0.48, 95% CI 0.24–0.96), income (lowest vs. highest income: aRR 1.67, 1.13–2.47) and the following mental health service use factors in pregnancy: admission (≥35 days/year vs. no days, aRR 4.54, 3.65–5.65), outpatient mental health care (no visits vs. ≥2 visits aRR 0.35, 0.27–0.47) and presence of a consistent mental health care provider during pregnancy (aRR 0.69, 0.54–0.89). Conclusion: Certain subgroups of women with schizophrenia may benefit from targeted intervention to mitigate risk for postpartum admission.